2002
DOI: 10.1148/radiol.2243011207
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Morphologic Evaluation of Congenital Urinary Tract Dilatation by Using Combined Static-Dynamic MR Urography: Findings in Kidneys with a Single Collecting System

Abstract: Combined static-dynamic MR urography provides high-quality depiction of the urinary tract in infants and children, while allowing accurate determination of single-kidney function and reliable evaluation of urinary excretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(75 citation statements)
references
References 45 publications
2
62
1
10
Order By: Relevance
“…MRU is effective in investigation of pediatric uropathological conditions and in the investigating of the congenital anomalies. It provides morphological and functional information (9).…”
Section: Radioisotope Investigationsmentioning
confidence: 99%
“…MRU is effective in investigation of pediatric uropathological conditions and in the investigating of the congenital anomalies. It provides morphological and functional information (9).…”
Section: Radioisotope Investigationsmentioning
confidence: 99%
“…The results achieved in the studies performed to evaluate MR urography and renal function numerically in literature are towards the possibility that it can be the alternative of the diuretic renal scintigraphy (Borthne et al, 2000;Avni et al, 2002;Rohrschneider et al, 2002;Zielonko et al, 2003). A dynamic MR urography technique that enables the calculation of single kidney function similarly with the scintigraphy was used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Rohrschneider et al [14] studied 62 patients of hydronephrosis using MRI and concluded that image quality was good or excellent in 95% of the cases. For split renal function, dMRI and isotope study showed significant correlation (r=0.92, p<0.001).…”
Section: Discussionmentioning
confidence: 99%